Chemotherapy-induced nausea and vomiting: exploring patients’ subjective experience - Zakaria, Noor Salihah; Mamat, Nik Mazlan; Lua, Pei Lin (Dove Medical Press Ltd., 2016)
Background: This study aimed to explore the subjective experience of nausea and vomiting during chemotherapy treatment among breast cancer patients and the impacts on their daily lives. Methods: A qualitative descriptive study was conducted in breast cancer patients who received chemotherapy and had experienced nausea and/or vomiting. Semi-structured interviews were conducted and analyzed using content analysis based on Giorgi’s method. Results: Of 15 patients who participated, 13 were included in the final analysis (median age =46 years, interquartile range [IQR] =6.0; all were Malays). Vomiting was readily expressed as the “act of throwing up”, but nausea was a symptom that was difficult to describe. Further exploration found great individual variation in patterns, intensity, and impact of these chemotherapy-induced nausea and vomiting (CINV) symptoms. While not all patients expressed CINV as bothersome, most patients described the symptom as quite distressing. CINV was reported to affect many aspects of patients’ lives particularly eating, physical, emotional, and social functioning, but the degree of impacts was unique to each patient. One of the important themes that emerged was the increase in worship practices and “faith in God” among Malay Muslim patients when dealing with these adverse effects. Conclusion: CINV continues to be a problem that adversely affects the daily lives of patients, hence requiring better understandings from the health care professionals on patients’ needs and concerns when experiencing this symptom.